The determinants of capital structure: Evidence from public listed companies in Malaysia, Singapore and Thailand - Jacinta Chan Phooi M'ng; Mahfuzur Rahman; Selvam Sannacy (Cogent Economics & Finance, 2017)
We investigate the determinants of capital structure of public listed companies on Bursa Malaysia, Singapore Stock Exchange and Thailand Stock Exchange from 2004 to 2013. We also investigate how firm-specific factors such as profitability, firm size, tangibility of assets and depreciation to total assets along with the macroeconomic factor such as inflation influence the capital structure decisions of public listed companies. Our findings support capital structure theories such as trade-off and pecking order theories and are consistent with prior empirical studies. We find all the factors examined in this study provide strong explanatory power for the capital structure decisions of the sampled public listed companies across all three countries. We find profitability has a significant negative influence on capital structure for Malaysia and Singapore but insignificant for Thailand. While, firm size has a significant positive influence on capital structure for all countries. Our findings also suggest that tangibility of assets has a significant positive influence on capital structure for Malaysia and Singapore while insignificant for Thailand. The depreciation to total assets indicates a negative influence on capital structure across all the three countries. Our study should be of interest to top managers who wish to have optimal capital structure to improve the firm performance.
Keywords: G31; G32; 330; capital structure; profitability; firm size; net tangible asset; depreciation to asset; inflation